2013
DOI: 10.1021/je301368x
|View full text |Cite
|
Sign up to set email alerts
|

Propylene and Propane Solubility in Imidazolium, Pyridinium, and Tetralkylammonium Based Ionic Liquids Containing a Silver Salt

Abstract: The gas solubility of propane and propylene in seven ionic liquids, 1-ethyl-3-methyl­imidazolium tetrafluoroborate (EMImBF4), 1-hexyl-3-methyl­imidazolium tetrafluoroborate (HMImBF4), 1-octyl-3-methyl­imidazolium tetrafluoroborate (OMImBF4), 3-methyl­imidazolium nitrate (BMImNO3), 1-butyl-3-methyl­imidazolium bis(trifluoro­methyl­sulfonyl­imide) (BMImTf2N), methyl­trioctyl­ammonium bis(trifluoro­methyl­sulfonyl­imide) (MOOONTf2N), and butyl­trimethyl­ammonium bis(trifluoro­methyl­sulfonyl­imide) (BMMMN Tf2N), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…A number of studies have utilized ionic liquids (ILs) as solvents to dissolve silver salts to improve separation performance. 23 27 ILs are a class of nonmolecular solvents with melting points lower than 100 °C. 28 ILs possess a number of desirable properties such as negligible vapor pressure that precludes their loss due to evaporation at elevated temperature, excellent thermal stability that extends the temperature range of the separation technique, and structural tunability that provides the capability of imparting desired selectivity toward target compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have utilized ionic liquids (ILs) as solvents to dissolve silver salts to improve separation performance. 23 27 ILs are a class of nonmolecular solvents with melting points lower than 100 °C. 28 ILs possess a number of desirable properties such as negligible vapor pressure that precludes their loss due to evaporation at elevated temperature, excellent thermal stability that extends the temperature range of the separation technique, and structural tunability that provides the capability of imparting desired selectivity toward target compounds.…”
Section: Introductionmentioning
confidence: 99%
“… 29 33 Fallanza and co-workers have evaluated the solubilities of propane and propylene in membrane separations using different combinations of imidazolium, pyridinium, and ammonium-based ILs and silver salts such as silver tetrafluoroborate, silver nitrate, and silver bis[(trifluoromethyl)sulfonyl]imide ([NTf 2 – ]). 23 It was found that anions of the silver salt and structural features of IL solvents strongly affect the olefin capacity and selectivity. Huang and co-workers applied silver-IL complexes, in which the silver(I) ion was a component of the cation, to separate olefin/paraffin mixtures using FTMs.…”
Section: Introductionmentioning
confidence: 99%
“…133 In this line, Ortiz et al 22,134 developed a material with promising characteristics for the separation of light olefin/paraffin mixtures. Previous to the material choice, a thorough investigation on the most suitable IL to form the IL/silver salt pair was carried out 135,136 . Among several pairs, 1-butyl-3-methylimidazolium tetrafluoroborate/silver tetrafluoroborate (BMImBF 4 /AgBF 4 ) was selected.…”
Section: Ionic Liquids For the Stabilization Of Ag +mentioning
confidence: 99%
“…The addition of silver salts to water or ionic liquids has been shown in the past to drastically enhance both, alkene capacity and selectivity due to the known chemical interaction of the alkene with the silver ion. [6][7][8][9][10][11][12][13][14] Aqueous silver nitrate and silver tetrafluoroborate solutions have been extensively studied and were close to commercialization in absorption/desorption processes. 10,15,16 Yet, both silver salts show tendencies to form explosive silver acetylides or decompose in aqueous environments.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, solutions of Ag[NTf 2 ], Ag [NO 3 ], Ag [BF 4 ] and Ag [OTf] in various ionic liquids have also been investigated with respect to their olefin uptake and their application in ene/ane separation processes has been suggested. [11][12][13][14] Dissolution of solid silver salts in an ionic liquid, however, always comes with a decrease in silver concentration and thus decreasing capacity for alkene complexation. Furthermore, an increase in viscosity with increasing silver concentration is generally observed, leading to slower mass transport.…”
Section: Introductionmentioning
confidence: 99%